Gingival and periodontal changes in patients undergoing in vitro fertilization treatment: A clinical study - Leena Smadi (Wolters Kluwer Medknow Publications, 2017)
Aims: The aim of this study was to investigate the effect of in vitro fertilization (IVF) treatment on different parameters of periodontal status. Settings and Design: This was a clinical observational study. Materials and Methods: One hundred and seventy-nine patients who underwent IVF treatment according to the standard IVF protocols were examined using the simplified oral hygiene, gingival index (GI), sulcus bleeding index (SBI), and determining the clinical attachment loss (CAL). A full-mouth examination except for the third molars was performed at 4 sites per tooth (mesiobuccal, distobuccal, mesiolingual, and distolingual). Periodontal evaluation was performed before infertility treatment, at the end of infertility treatment, and 14 days after embryo transfer. Statistical Analysis: The Kruskal-Wallis or Fisher's tests were used to compare the median or mean values as appropriate. Results: The oral hygiene index simplified was 0.49, 0.32, and 0.37 at pretreatment, on the day of human chorionic gonadotropin (HCG) trigger, and on the day of the pregnancy test, respectively. The GI showed significant differences before and after treatment. The mean GI was 0.13 at pretreatment compared to 0.51 and 0.53 on the days of HCG trigger and of the pregnancy test, respectively. The same trend was seen for SBI. There were no differences in CAL among the three examinations. There was no difference between the two groups except for GI (0.71 vs. 0.48 for a positive pregnancy test vs. nonpregnancy, respectively). Conclusions: IVF medications and a superphysiological condition affect oral health, particularly gingival and periodontal statuses, and likely complicate the relationship between infertility, sex hormones, and infertility management. Larg-scale studies are needed to confirm the effect of such treatment on oral health.